2013
DOI: 10.1093/ndt/gft300
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic equivalence and pharmacokinetics of generic tacrolimus formulation in de novo kidney transplant patients

Abstract: Therapeutic equivalence and the PK of GEN tacrolimus should be evaluated in patients undergoing de novo renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…Five studies including 365 patients after LT (191 de novo, 174 conversion) and nine studies including 883 patients after KT (735 de novo, and 148 conversion) compared BPAR of patients on generic Tac with those on innovator Tac after LT or KT, all of them in a parallel design (Table ). However, only two of those studies were randomized controlled trials and a further two were non‐randomized prospective studies . Risk ratios for BPAR rates of patients on generic Tac versus innovator Tac were compared in a forest plot stratified visually by organ and study design (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies including 365 patients after LT (191 de novo, 174 conversion) and nine studies including 883 patients after KT (735 de novo, and 148 conversion) compared BPAR of patients on generic Tac with those on innovator Tac after LT or KT, all of them in a parallel design (Table ). However, only two of those studies were randomized controlled trials and a further two were non‐randomized prospective studies . Risk ratios for BPAR rates of patients on generic Tac versus innovator Tac were compared in a forest plot stratified visually by organ and study design (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Data are presented as mean±SD. 17 This may indicate that aging is not the main parameter responsible for the nonbioequivalence observed in our study. of the intended patient population.…”
Section: Discussionmentioning
confidence: 68%
“…T max was analyzed using Wilcoxon signed rank test. 16,17,[20][21][22][23] Alloway et al 16 conducted the first prospective study specifically designed to compare the steady-state PK of a generic Tac formulation to the original drug in renal transplant recipients. AUC 0-12 , area under the plasma concentration versus time curve from zero to 12 hr; CI, confidence interval; C max , maximum whole blood concentration; T max , time to C max ; C 0 , concentration before the dose; Tac, tacrolimus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no unexpected serious adverse events. The other trial was a pharmacokinetic study in KT recipients to compare the pharmacokinetic parameters of the original and the generic tacrolimus 18. This study showed that the generic tacrolimus had an earlier and higher C max than the original tacrolimus.…”
Section: Discussionmentioning
confidence: 99%